Representation of Millennial Generation in the Film Called My Generation - M. Mujahidin Alhaq; Nur Maghfirah Aesthetika (Indonesian Journal of Cultural and Community Development, 2022)
The millennial generation is hotly discussed among us. My Generation film tries to tell the story of how life is, how the figure of the millennial generation is actually, by carrying the four main characters Zeke, Suki, Orly and Konji. Because all this time we know that the millennial generation is a technology literate generation. Therefore, this study aims to find out how the millennial generation characters in the film My generation are. This study uses descriptive qualitative research methods, and the analytical technique used in this study is Charles Sanders Pierce's semiotics. The results of the analysis show that the representation of the millennial generation in the film My Generation, is a generation that has different characters from the previous generation, they are more daring to voice what they feel, what they think, dare to try new things and do not hesitate to see things from their point of view.